Parietal Cortex Connectivity as a Marker of Shift in Spatial Attention Following Continuous Theta Burst Stimulation - Mariner, Jessica; Loetscher, Tobias; Hordacre, Brenton (Frontiers in Human Neuroscience, 2021)
Non invasive brain stimulation is a useful tool to probe brain function and provide therapeutic treatments in disease. When applied to the right posterior parietal cortex (PPC) of healthy participants, it is possible to temporarily shift spatial attention and mimic symptoms of spatial neglect. However, the field of brain stimulation is plagued by issues of high response variability. The aim of this study was to investigate baseline functional connectivity as a predictor of response to an inhibitory brain stimulation paradigm applied to the right PPC. In fourteen healthy adults (9 female, aged 24.8 ± 4.0 years) we applied continuous theta burst stimulation (cTBS) to suppress activity in the right PPC. Resting state functional connectivity was quantified by recording electroencephalography and assessing phase consistency. Spatial attention was assessed before and after cTBS with the Landmark Task. Finally, known determinants of response to brain stimulation were controlled for to enable robust investigation of the influence of resting state connectivity on cTBS response. We observed significant inter-individual variability in the behavioral response to cTBS with 53.8% of participants demonstrating the expected rightward shift in spatial attention. Baseline high beta connectivity between the right PPC, dorsomedial pre-motor region and left temporal-parietal region was strongly associated with cTBS response (R2 = 0.51). Regression analysis combining known cTBS determinants (age, sex, motor threshold, physical activity, stress) found connectivity between the right PPC and left temporal-parietal region was the only significant variable (p = 0.011). These results suggest baseline resting state functional connectivity is a strong predictor of a shift in spatial attention following cTBS. Findings from this study help further understand the mechanism by which cTBS modifies cortical function and could be used to improve the reliability of brain stimulation protocols.